Penerapan Gamifikasi Powtoon Dan Quizizz dalam Meningkatkan Motivasi Belajar Akidah Akhlak Siswa SMA Negeri 6 Palangka Raya - Nurul Ahmat Fauzi; Jasiah Jasiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research aims to produce a Gamification learning model based on Powtoon and Quizizz in increasing the motivation to learn moral beliefs of students at SMA Negeri 6 Palangka Raya. The method used is SAM 1 (Successive Approximation Model). This model consists of three stages, namely evaluation (analysis), design and development which are repeated in three cycles (iterative). Ends with an evaluation (expert review) by media experts, learning design experts and material experts. The evaluation applied is formative evaluation using an open concept. The gamification learning module developed integrates interesting animated videos from Powtoon and interactive quizzes from Quizizz to present moral belief material in a more interesting and interactive way. The research subjects were class X students with a sample size of 20 people. The techniques and instruments used are observation, interviews and questionnaires. The subject was attempted by media experts, material experts, teaching experts and class X students of SMA N 6 Palangka Raya. The results of expert observations state that the gamification of Powtoon and Quizizz can be used as a learning medium to increase motivation to learn moral beliefs, which is also supported by the score achieved in the formative evaluation with a value of 3.4, which means very good